DNA barcoding of Burgo chicken from Bengkulu, Indonesia, based on the cytochrome oxidase gene sub unit I mitochondria DNA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Utama AF, Jarulis, Sipriyadi, Jannah IM. 2023. DNA barcoding of Burgo chicken from Bengkulu, Indonesia, based on the cytochrome oxidase gene sub unit I mitochondria DNA. Biodiversitas 24: 6268-6275. The Burgo chicken provides a genetic source of one crossbreed chicken in Bengkulu Province. However, genetic information on Burgo chickens is not yet available, while the population of this chicken continues to decline. Research on DNA barcoding using the cytochrome oxidase subunit I mtDNA gene was conducted to obtain DNA barcodes and the relationship between Burgo chickens and other chicken species based on the COI mtDNA gene. Blood samples were obtained from Burgo chickens belonging to the Bengkulu Burgo chicken hobbyist community. Collected blood was isolated following the dneasy® blood and tissue kit protocol based on the spin-column protocol procedure, Qiagen. Amplification of genomic DNA using Polymerase Chain Reaction. The product was electrophoresed on a 1.2% agarose gel and visualized under UV light using Gel Documentation System, Axygen. Samples with bright DNA bands proceeded to the sequencing process. Sequencing results were analyzed using MEGA 11.0 software. The results showed that the target length of the Burgo chicken band was in accordance with the primer design used (752pb). SNPs were obtained at 10 specific sites in Burgo chickens and had a species barcode at site 746. The intraspecies genetic distance was 0.6%, interspecies 1.2%, and with the outgroup 14.5%, there were 12 haplotypes from all samples (n=15). Based on the result, we can conclude that the Burgo chicken is closely related to the red jungle fowl compared to other chicken species.